THE MOST COMMON ENDOCRINOLOGICAL DISORDERS IN PREGNANCY - Milovanović, Zagorka (Medicinski podmladak, 2024)
Pregnancy is a state of disturbed physiological mechanisms, affecting almost all systems of organs. Endocrine disorders that occur during pregnancy can significantly impact maternal and fetal health, necessitating a comprehensive understanding of their etiology, diagnosis, and management. The most common endocrinological disorders during pregnancy are gestational diabetes and thyroid gland dysfunctions. Diabetes during pregnancy carries a higher risk of complications, such as preeclampsia, preterm birth, macrosomia, and cesarean delivery. However, with careful management, numerous women with diabetes can have healthy pregnancies and deliver healthy babies. Hypothyroidism during pregnancy refers to an underactive thyroid gland function, where the thyroid gland doesn’t produce enough thyroid hormones, particularly thyroxine (T4) and triiodothyronine (T3). This condition can have significant implications for the mother and the developing fetus. Untreated hypothyroidism may lead to severe complications, including intellectual and developmental issues in the child, preeclampsia, anemia, miscarriage, or preterm birth. Aside from these two of the most common endocrinological dysfunctions, maternal and fetal well-being can be significantly affected by other endocrine gland disorders, such as parathyroid, adrenal, and pituitary gland disturbances. If unrecognized or untreated, all these conditions can lead to poor pregnancy and maternal outcomes. Endocrinological disorders during pregnancy represent a complex and critical area of concern for both maternal health and fetal development. Furthermore, they can have far-reaching implications that extend beyond the duration of pregnancy, having lifelong implications for the future mother and the offspring. Effective management of endocrinological disorders in pregnancy requires a multidisciplinary team approach involving obstetricians, endocrinologists, nutritionists, and other healthcare professionals. Timely interventions, personalized treatment plans, and close monitoring are at the core of optimal obstetric care for these patients. Lifestyle modifications, medication adjustments, and regular prenatal care play crucial roles in optimizing maternal health and birth outcomes.